Prevalence and virulence genes of Staphylococcus aureus from food contact surfaces in Thai restaurants - Tasanapak, Kannipa; Kucharoenphaibul, Siriwat; Wongwigkarn, Jintana; Sitthisak, Sutthirat; Thummeepak, Rapee; Chaibenjawong, Plykaeow; Chatdumrong, Wassana; Nimanussornkul, Kunsuda (PeerJ, 2023)
Background Staphylococcus aureus is one of the most common pathogens responsible for food poisoning due to its ability to produce staphylococcal enterotoxin (SE). S. aureus can form biofilms on the surfaces of food processing devices, enabling the distribution of SE on foods through cross-contamination events. Thailand is known for its exotic cuisine, but there is no data on the prevalence of SE-harboring S. aureus in restaurants in Thailand. Methods In this study, we conducted surface swabs on surfaces of kitchen utensil that come into contact with food and on the hands of food handlers working in restaurants in the north part of Thailand. Isolated S. aureus was investigated for biofilm formation, virulence, and SE genes. Results Two hundred S. aureus were isolated from 650 samples. The highest prevalence of S. aureus contamination was detected on the hands of food handlers (78%), followed by chopping boards (26%), plates (23%), knives (16%), spoons (13%), and glasses (5%). All of them were methicillin-sensitive S. aureus (MSSA) and the mecA gene was not present in any strains. Biofilm formation was detected using the CRA method, and 49 (24.5%) were identified as biofilm-producing strains, with the hands of food handlers identified as the primary source of biofilm-producing strains. The prevelence of biofilm-related adhesion genes detected were: icaAD (13%), fnbA (14.5%), cna (6.5%), and bap (0.5%). Two classical enterotoxin genes, sec and sed, were also found in four and six of the S. aureus isolates, respectively, from hands and utensils. Conclusion The highest prevelence of S. aureus was detected on the hands of food handlers. S. aureus strains with biofilm and enterotoxin production abilities were discovered on food contact surfaces and the hands of food handlers, implying significant risk of food contamination from these sources that could be harmful to consumers. To avoid cross-contamination of food with food contact items, the food handlers’ hands should be properly washed, and all food preparation equipment should be thoroughly cleaned.
Keywords: S. aureus; Virulence gene; Food contact article; Cross-contamination